"Did You Teach Us to Do Otherwise?": Young Women in the Tsukunft Youth Movement in Interwar Poland and Their Role Models. Issue 1 (1st March 2020) - Kozłowska, Magdalena
Abstract: The article deals with the issue of Jewish youth movements' contribution to women's empowerment in interwar Poland using the example of the socialist movement Tsukunft. The article explores the movement's politics of memory in the interwar period and the selection of heroines whom the young women of Tsukunft were supposed to emulate, as well as real-life examples of Bundist women activists of the interwar period who served them as role models. In its examination of this alternative to the examples proposed by the mainstream state narrative, the article offers a view of Jewish social life in Poland, but also asks more specific questions, such as the true nature of relationships between Bundist women and men.